2022
DOI: 10.1007/s11356-022-19775-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substrate properties and phosphorus supply on facilitating the uptake of rare earth elements (REE) in mixed culture cropping systems of Hordeum vulgare, Lupinus albus and Lupinus angustifolius

Abstract: This study presents how phosphate (P) availability and intercropping may influence the migration of rare earth elements (REEs) in legume–grass associations. In a replacement model, Hordeum vulgare was intercropped with 11% Lupinus albus and 11% Lupinus angustifolius. They were cultivated on two substrates, A (pH = 7.8) and B (pH = 6.6), and treated with 1.5 g P m−2 or 3 g P m−2. Simultaneously, a greenhouse experiment was conducted to quantify carboxylate release. There, one group of L. albus and L. angustifol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…On the other hand, the species-and variety-dependent effect of PG on the heavy metal contents observed in our experiment might be explained by different strategies being developed in various lupin species to efficiently extract phosphorus, and thus contributing differently to the modification of conditions in the rhizosphere (Pearse et al 2006, Lambers et al 2013, Ding et al 2021, Aslam et al 2021, Monei et al 2022). However, a complete explanation of this phenomenon requires a more thorough analysis and goes beyond the scope of this work.…”
Section: Cadmium and Lead Content In Soil Materialsmentioning
confidence: 78%
See 1 more Smart Citation
“…On the other hand, the species-and variety-dependent effect of PG on the heavy metal contents observed in our experiment might be explained by different strategies being developed in various lupin species to efficiently extract phosphorus, and thus contributing differently to the modification of conditions in the rhizosphere (Pearse et al 2006, Lambers et al 2013, Ding et al 2021, Aslam et al 2021, Monei et al 2022). However, a complete explanation of this phenomenon requires a more thorough analysis and goes beyond the scope of this work.…”
Section: Cadmium and Lead Content In Soil Materialsmentioning
confidence: 78%
“…4), in particular in narrow--leaf lupin, observed here as a result of the PG application, might be explained in two ways. Firstly, the introduction of an additional pool of phosphorus into the soil may contribute to an increased production and secretion of organic acids from roots, which under certain conditions can chelate toxic elements, and thus limit their availability to plants (Rӧmer et al 2000, Monei et al 2022). The released citrate can complex up to 85% of Cd, but this effect is highly dependent on the type of soil (Rӧmer et al 2000).…”
Section: Cadmium and Lead Content In Plant Tissuementioning
confidence: 99%
“…Processes during uptake sometimes fractionate only one specific REE, as demonstrated for Eu [234,258], Sm, Tb, and Nd [258]. When the evaluation of REE accumulation in plants growing in their natural growth environment is desired, it has to be noticed that REE availability is significantly influenced by interspecific root interactions [73,74,259] that impact not only the total level of REE accumulation but also the fractionation pattern of REE in plant communities. In addition, plant recycling modifies REE speciation since uptake preferentially affects weakly bound REE pools, which are returned into the soil as REE bound into organic matter [5,30].…”
Section: Biosphere 71 Plant Availability and Accumulation Of Ree In H...mentioning
confidence: 99%
“…In contrast, the exudation of carboxylates by L. albus would be inducible, because the plants' Mn concentration changed in response to the soil's PBray1 availability [72]. Monei et al [74], who also noted a divergent response in these lupine species, found that L. albus exhibited a high release of carboxylates in conditions of P deficiency, whereas L. angustifolius responded with the highest release of carboxylates when the soil had a high P supply. Although there was no clear relationship between Mn concentrations and plants' P contents or soil's P availability in both lupines across all sites in the current study, there was a significant association between the soil acidity at harvest and the Mn concentration; however, it was noticeably different between the lupine species.…”
Section: Effects Of Species and Soil Types: Links Between Traits Of S...mentioning
confidence: 99%